CSC533: Multimedia Programming / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2023)
This course will introduce the students to the world of multimedia programming. It relates the student knowledge of elementary multimedia and further expands it to a higher level. The topics include introduction to multimedia, abstraction for multimedia programming, object-oriented multimedia, multimedia framework, media computation & manipulation and research problems in multimedia programming.